Achieving ultrahigh electrochemical performance by surface design and nanoconfined water manipulation. Issue 6 (27th April 2022) - Li, Haisheng; Xu, Kui; Chen, Pohua; Yuan, Youyou; Qiu, Yi; Wang, Ligang; Zhu, Liu; Wang, Xiaoge; Cai, Guohong; Zheng, Liming; Dai, Chun; Zhou, Deng; et al.
Abstract: The effects of nanoconfined water and the charge storage mechanism are crucial to achieving the ultrahigh electrochemical performance of two-dimensional transition metal carbides (MXenes). We propose a facile method to manipulate nanoconfined water through surface chemistry modification. By introducing oxygen and nitrogen surface groups, more active sites were created for Ti3 C2 MXene, and the interlayer spacing was significantly increased by accommodating three-layer nanoconfined water. Exceptionally high capacitance of 550 F g –1 (2000 F cm –3 ) was obtained with outstanding high-rate performance. The atomic scale elucidation of the layer-dependent properties of nanoconfined water and pseudocapacitive charge storage was deeply probed through a combination of 'computational and experimental microscopy'. We believe that an understanding of, and a manipulation strategy for, nanoconfined water will shed light on ways to improve the electrochemical performance of MXene and other two-dimensional materials. Abstract : Record-breaking electrochemical energy storage performance achieved in titanium carbides (MXenes) by surface design and nanoconfined water manipulation, with its atomic mechanism revealed.